Libri cafe: Kolaborasi kafe dan perpustakaan sebagai sarana learning commons dalam upaya meningkatkan literasi informasi pemustaka : (Studi Kasus Perpustakaan Universitas Syiah Kuala) - Uci Elisa Pitri (IJAL (Indonesian Journal of Academic Librarianship), 2021)
The rapid development of this era is certainly a challenge for the world of libraries considering that the library is now starting to leave the library that becomes a source of information and switch to more sophisticated information systems. Based on this, the library needs to make a new breakthrough to maintain its existence and attract reading interest and evaporate the ability of information literacy to continue to grow. This article discusses the cooperation or collaboration carried out by libraries and cafes in improving literacy and also the desire to visit the libraries of Syiah Kuala University and Coffe Cho. With this article is expected to be an inspiration for readers to be able to pour ideas that seek to maintain the existence of libraries and also to attract reading interests and improve public literacy.